2008
DOI: 10.1088/0004-6256/136/3/1147
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleus of the Sagittarius DSPH Galaxy and M54: A Window on the Process of Galaxy Nucleation

Abstract: We present the results of a thorough study of the nucleus of the Sgr dwarf spheroidal galaxy (Sgr dSph) and of the bright globular cluster M54 (NGC 6715) that resides within the same nucleus (Sgr,N). We have obtained accurate radial velocities and metallicity estimates for 1152 candidate Red Giant Branch stars of Sgr and M54 lying within ∼ 9 ′ from the center of the galaxy, from Keck/DEIMOS and VLT/FLAMES spectra of the infrared Calcium II triplet. Using both velocity and metallicity information we selected tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
270
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(298 citation statements)
references
References 111 publications
26
270
2
Order By: Relevance
“…It has been suggested that ω Cen may be the remnant of the nucleus of a, now destroyed, dwarf galaxy that had hosted a globular cluster (GC) at its center (Bellazzini et al 2008;Carretta et al 2010). ω Cen would then be a system similar to the GC M 54 plus the nucleus (SgrN) of the Sagittarius dwarf spheroidal galaxy (Sgr dSph) at whose center it lies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ω Cen may be the remnant of the nucleus of a, now destroyed, dwarf galaxy that had hosted a globular cluster (GC) at its center (Bellazzini et al 2008;Carretta et al 2010). ω Cen would then be a system similar to the GC M 54 plus the nucleus (SgrN) of the Sagittarius dwarf spheroidal galaxy (Sgr dSph) at whose center it lies.…”
Section: Discussionmentioning
confidence: 99%
“…It is sufficiently massive to contain more than one stellar population, as indicated by helium abundance variations (Norris 2004;Piotto et al 2005) and its peculiar position in the sizeluminosity plane (Mackey & van der Bergh 2005). It has been also argued that ω Cen may not be a genuine globular cluster but the nuclear remnant of a dwarf galaxy that merged in the past with the Milky Way (e.g., Bellazzini et al 2008).…”
Section: Radial Velocity Measurements For ω Centaurimentioning
confidence: 99%
“…With the discovery of Sgr dSph, 4 globular clusters (GC) which were before considered belonging to the halo have been recognized as being associated with the Sgr dSph. While three of them (Terzan 7, Terzan 8, and Arp 2) lay at the outskirts of Sgr dSph, the position of the fourth one, M 54, coincides with the center of the dwarf spheroidal (Monaco et al 2005b) although it likely formed elsewhere and fell subsequently into the galaxy core (Bellazzini et al 2008). It became subsequently clear that a number of other globular clusters, currently lying far from Sgr dSph, have kinematical properties compatible with an origin within the Sgr dSph system, and a subsequent stripping (Bellazzini et al 2003), or were actually embedded into the stream material (Martínez-Delgado et al 2002).…”
Section: Introductionmentioning
confidence: 99%